Multithread Approximation: A new OpenMP construct - Oliveira, João B.; Gonçalves, Rogério A.; Fabrício Filho, João (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD), 2024)
This study presents a new construct in OpenMP designed to facilitate the implementation of approximate computing techniques within parallel programming environments. By integrating approximation methods such as task dropping, loop perforation, and floating-point relaxation, the proposed construct aims to enhance performance and energy efficiency while maintaining acceptable accuracy levels. Experimental results on benchmark applications demonstrate a trade-off of up to 490.83%, with 55.1% of quality loss, highlighting the potential and limitations of approximate computing in parallel contexts.